Efektivitas Penyuluhan Pertanian dalam Pengembangan Usaha Tani Semangka di Desa Jetis, Kecamatan Nusawungu, Kabupaten Cilacap - Nurlaila Fatmawati; Umi Barokah; Hasanurdin Hasanurdin (Program Studi Magister Agribisnis, Universitas Sebelas Maret, 2025)
Agricultural extension plays a crucial role in enhancing farmers’ capacity to adopt cultivation technologies, thereby improving productivity and ensuring the sustainability of farming systems, including watermelon production. This study aims to examine the effectiveness and achievement of watermelon agricultural extension activities in Jetis Village, Nusawungu Sub-district, Cilacap Regency. The research population consisted of 187 watermelon farmers who were members of farmer groups, from which 50 respondents were selected using a stratified random sampling method. Data were collected through observations, individual and group interviews, and documentation, and analyzed using qualitative and quantitative approaches. The effectiveness of extension activities was assessed based on the level of adoption of thirteen watermelon cultivation technology packages, including the use of improved seeds, planting techniques, crop maintenance, fertilization practices, pest and disease control, pesticide use, post-harvest handling, processing of watermelon products, communication language, training activities, farmer guidance and motivation for land expansion, and market information dissemination. The results indicate that the effectiveness of watermelon agricultural extension in Jetis Village falls into the very effective category, with an average interval score of 60.76, indicating that extension activities have been successfully implemented in accordance with the recommended technology packages from cultivation to marketing stages. Furthermore, the achievement of extension implementation is also classified as very effective, with an average interval score of 61.58, reflecting the extension agents’ ability to deliver extension materials clearly, communicatively, and in a manner that is easily understood by farmers, thereby encouraging the optimal adoption of watermelon cultivation technologies.